Excretion of Heavy Metals and Glyphosate in Urine and Hair Before and After Long-Term Fasting in Humans - Grundler, Franziska; Séralini, Gilles-Eric; Mesnage, Robin; Peynet, Vincent; Wilhelmi de Toledo, Françoise (Frontiers in Nutrition, 2021)
Background: Dietary exposure to environmental pollutants in humans is an important public health concern. While long-term fasting interrupts the dietary exposure to these substances, fat mobilization as an energy source may also release bioaccumulated substances. This was, to our knowledge, only investigated in obese people decades ago. This study explored the effects of 10-days fasting on the excretion of heavy metals and glyphosate. Methods: Urinary levels of arsenic, chromium, cobalt, lead, nickel, mercury and glyphosate were measured before and after 10 fasting days in 109 healthy subjects. Additionally, hair analysis was done before and ten weeks after fasting in 22 subjects. Results: Fasting caused a decrease in body weight, and in urinary arsenic (by 72 %) and nickel (by 15 %) concentrations. A decrease in lead hair concentrations (by 30 %) was documented. Urinary mercury levels were unchanged for chromium, cobalt and glyphosate, which were undetectable in most of the subjects. Additionally, fatigue, sleep disorders, headache and hunger were reduced. Body discomfort symptoms diminished four weeks after food reintroduction. Conclusions: The results of this study provide the first insights into the changes in heavy metal excretion caused by long-term fasting. Further studies focusing on the kinetics of efflux between different compartments of the body are needed.